Pengembangan Komik Matematika Berbasis Problem Based Learning Pada Materi Bangun Ruang Sisi Datar di SMP Negeri Semangus Kelas VIII - Mutiara Lesa Puspita Sari; Luthfiana, Maria; Elly, As (FKIP Universitas Mataram, 2024)
This research aums to produce a Mathematical Comic Based on Problem Based Learning on Flat Side Building Material for Class VIII that is valid, practical, and has potential effects. This research is development research using ADDIE development model, which consists of stages: analysis, design, development, implementation and evaluation. Data collection techniques were carried out through interviews, obsertionnaires and tests, with the research subjects being class VIII students class VIII students at Semangus State Middle School, totaling 6 students for the small group test and 15 students for the field test. Based on the results of data analysis, it shows that the Aiken’s V value from language expert validation is 0.80, media expert 0.72, and material expert is 0.77 in the valid category. In the teacher practicality test it was 85% and the student practicality test was 80.71% in the very practical category. In the practicality test, teacher, and students obtained and overall percentage of 81.41% in the very practical category. And the results of the potential effects given by 15 students showed that 13 students (87%) were in the completed category and 2 students (13%) were in the incomplete category.